BUDIDAYA BELUT DI LAHAN MINIMALIS DAN PRODUK OLAHANNYA SEBAGAI PELUANG USAHA - Said Rizki Ananda; Andre Saputra; Ade Melda; Zelika Novtalia; Diyah Ayu Putri Maharani (Nusantara Hasana Journal, 2023)
Eels belong to a group of snake-shaped fish belonging to the Synbranchidae tribe. Eels can live in fresh water areas, swamps, rice fields, fish ponds and lakes. Usually eels eat small fish as food. Besides that, eel has several different types. If consumed, eel has a fairly high content value compared to eggs and meat. Because of this high content value that makes eel a good food for consumption. Because there are so many advantages that eels have, that's why the development of eel cultivation is carried out. The development of eel cultivation is expected to increase the productivity of eel products, because eels that come from nature are now small in population due to fishing that is not environmentally friendly and the use of chemical fertilizers in the rice fields causes damage to the eel ecosystem is disrupted. The scarcity of eels that are found in nature causes eels circulating in the market to be difficult to find and have a fairly high selling price. This is what underlies the need for home eel cultivation by using drums or making small ponds. The purpose of the activity is to produce quality eels by cultivating at home by making eel houses. To produce a home-made product that is nutritious and liked by various groups of people because it tastes delicious. To promote processed eel products through the marketplace.